Cognitive Functioning in Trichotillomania Across the Lifespan. (January 2021) - Gladstone, Theresa R.; Wilton, Emily P.; Luke, Anna K.; Flessner, Christopher A.; Grant, Jon E.
Highlights: Trajectory of executive functions may be different in people with Trichotillomania Inhibitory control may be stable over the lifespan No significant differences were found in cognitive flexibility across the lifespan Future research with longitudinal methods may suggest targeted interventions